A Rare Case of Isolated Ureteral Diaphragmatic Herniation: Case Report and Review of Literature - Nassib Abou Heidar; Hussein Elsemesmani; Ahmad Elamine; Mustafa Natout (Case Reports in Urology)
Diaphragmatic ureteral hernias are rare causes of ipsilateral renal obstruction. Management strategies varies from conservative to ureteral stenting to operative herniorraphy and reduction. We present a case of a 71-year-old man who was found to have an incidental right ureteral diaphragmatic herniation causing an asymptomatic kidney obstruction. He was managed conservatively with no evidence of increased hydronephrosis on serial imaging and no deterioration of biochemical renal function. We review all similar cases published in the literature and discuss the optimal treatment strategies.